2022
DOI: 10.3389/fenrg.2021.771697
|View full text |Cite
|
Sign up to set email alerts
|

Building Structure-Property Relationships of Cycloalkanes in Support of Their Use in Sustainable Aviation Fuels

Abstract: In 2018 13.7 EJ of fuel were consumed by the global commercial aviation industry. Worldwide, demand will increase into the foreseeable future. Developing Sustainable Aviation Fuels (SAFs), with decreased CO2 and soot emissions, will be pivotal to the on-going mitigation efforts against global warming. Minimizing aromatics in aviation fuel is desirable because of the high propensity of aromatics to produce soot during combustion. Because aromatics cause o-rings to swell, they are important for maintaining engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Recently, Landera et al sought to gain information on cycloalkane behavior for use with sustainable aviation fuels. 30 Part of the screening process used to select surrogate components involves examining the physical properties that are important for engine systems, including density and viscosity. The density and viscosity influence the formation of droplets in the combustion chamber, and bulk modulus, which depends on speed of sound and density, affects the start of injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Landera et al sought to gain information on cycloalkane behavior for use with sustainable aviation fuels. 30 Part of the screening process used to select surrogate components involves examining the physical properties that are important for engine systems, including density and viscosity. The density and viscosity influence the formation of droplets in the combustion chamber, and bulk modulus, which depends on speed of sound and density, affects the start of injection.…”
Section: Introductionmentioning
confidence: 99%
“…Cycloalkanes and linear alkanes are two of the main groups that can make up a significant portion of liquid fossil fuels (e.g., ∼20 to 47% for Jet A) and sustainable fuels (e.g., 60% for sustainable aviation fuel). Representatives from these classes of compounds are often included in formulations of simple mixture systems (surrogate mixtures) to model the real fuel that can contain hundreds of compounds. ,,,, Dooley et al found that the reactivity of a surrogate mixture containing a cycloalkane better matched the real fuel reactivity than did a surrogate without cycloalkanes. Recently, Landera et al sought to gain information on cycloalkane behavior for use with sustainable aviation fuels . Part of the screening process used to select surrogate components involves examining the physical properties that are important for engine systems, including density and viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jet-A (POSF-10325) fuel typically contains an average of 32 wt % total cycloalkanes including both mono- and bicyclic alkanes . When 10 or 30 wt % of cycloalkanes is added to Jet-A, the cycloalkane content in the standard fuel increases from 32 wt % to 40 or 52 wt %, respectively . There is an urgent need to understand the changes in the physical and chemical properties of the fuel based on varied percentages of different blended components of SAFs to explore how energy is stored within the structures of the cycloalkanes, to establish the structure–property relationship, and ultimately to rationally design new cycloalkanes for SAFs.…”
Section: Development Of Sustainable Aviation Fuelsmentioning
confidence: 99%
“…Incomplete combustion of cycloalkanes at high temperatures can also potentially lead to production of polycyclic aromatic hydrocarbons and soot particles. 13,14 At low temperatures, cycloalkanes tend to be less reactive than the corresponding linear alkanes because of conformational strain imposed by the ring. 14,15 Cyclohexane is a typical cycloalkane that exhibits the common characteristics of a cyclic hydrocarbon and can serve as a general model for understanding cycloalkane reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic hydrocarbons can make up a large fraction (15–40%) of traditional transportation fuels and their content can be up to 100% in unconventional fuels, including coal-based synthetic, shale-derived, and biomass fuels. A recent study suggests that cycloalkanes can be useful in developing sustainable aviation fuels by reducing the need for aromatic additives, which have high soot formation propensity during combustion. Incomplete combustion of cycloalkanes at high temperatures can also potentially lead to production of polycyclic aromatic hydrocarbons and soot particles. , At low temperatures, cycloalkanes tend to be less reactive than the corresponding linear alkanes because of conformational strain imposed by the ring. , …”
Section: Introductionmentioning
confidence: 99%